Presupposition on Barack Obama’s Speech at Islamic Society of Baltimore - Ricky Ade Saputra; Zahrida zahrida; Gita Mutiara Hati (Journal of English Education and Teaching, 2021)
This research aimed to find out the kinds of presupposition on Barrack Obama’s speech at Islamic Society of Baltimore. In this research, the researchers used a descriptive qualitative method. The object of this research is the script in the Barrack Obama speech. Instrument of this research is observational checklist. It means that the researcher watches the video of Barrack Obama’s speech at Islamic Society of Baltimore. The video can be function to see context the utterances. The researcher finds the data on the script of Barrack Obama’s speech. The researcher provides the table of presupposition for analyzing data. Table of potential presupposition is the instrument used by researcher to put the data, to classify and to identify the data. The mostly types of presupposition found in Barrack Obama’s speech at Islamic society of Baltimore is existential presupposition and the less is lexical presupposition. The existential presupposition was the most dominant on this speech because the speeches contain more define descriptive, real fact and real information to stimulate the audience’s attention and emphasize his idea and promises to keep Muslim American feeling safe in minority. Lexical in this research is the lowest number of type’s presupposition on speeches of Barack Obama. This means that in the Barack Obama's speech there was no implied expression to confirm his opinion.